2022
DOI: 10.1136/bmj-2021-069164
|View full text |Cite|
|
Sign up to set email alerts
|

Variation in revascularisation use and outcomes of patients in hospital with acute myocardial infarction across six high income countries: cross sectional cohort study

Abstract: Objectives To compare treatment and outcomes for patients admitted to hospital with a primary diagnosis of ST elevation or non-ST elevation myocardial infarction (STEMI or NSTEMI) in six high income countries with very different healthcare delivery systems. Design Retrospective cross sectional cohort study. Setting Patient level administrative data from the United States, Canada (Ontario and Manitoba), Engla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…We applied the same inclusion and exclusion criteria in the same order in each country, although some variations to reflect local differences in data architecture were allowed. More detail is available elsewhere on the data sources used for each country …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We applied the same inclusion and exclusion criteria in the same order in each country, although some variations to reflect local differences in data architecture were allowed. More detail is available elsewhere on the data sources used for each country …”
Section: Methodsmentioning
confidence: 99%
“…From prior work, recording of comorbidities differs markedly across countries due to different incentives for coding . As a result, adjusting for recorded comorbidities in between-country comparisons is likely biased.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Samsky et al reported that reductions in 30-day readmission rates for heart failure in Canada between 2005 and 2015 were similar to those observed in the US. Cram et al found that reductions in readmissions for myocardial infarction observed in the US between 2011 and 2017 were matched in Canada, the Netherlands, Israel, and Taiwan.…”
mentioning
confidence: 99%
“…If you made these choices, how could professionals and the public be confident that you will take full advantage of the opportunity of a data-centric health service, including a full and frank conversation about companies’ use of health data (doi:10.1136/bmj.o1018)?13 Could you be trusted with striking new evidence that joint injections for osteoarthritis are potentially beneficial and help us rethink osteoarthritis as a disease of tear, flare, and repair instead of wear and tear (doi:10.1136/bmj-2021-068446, doi:10.1136/bmj.o1028)?1415 Or be relied on to learn the lessons from a multinational study of outcomes after revascularisation for acute myocardial infarction (doi:10.1136/bmj-2021-069164)?16 And you would probably struggle to maximise the clear potential of telemedicine for surgery, a potential that is being realised in the international support for the surgeons and people of Ukraine (doi:10.1136/bmj.o1078). 17…”
mentioning
confidence: 99%